Estimación del indicador de calidad de vida para el Área Metropolitana de Medellín (2010)
ABSTRACT: This paper presents/displays the estimation of the Indicator of Quality of Life (ICV) for the homes in the municipalities of the Metropolitan Area of the Valley of Aburrá for year 2009 you base on the information proporcinada by the Encusta of Quality of Life 2009. The used statistical methodology is based on the use of the methods of Quantification of Qualitative Variables and the Analysis Nonlinear of Main Components. A description of this methodology is in Young (1981), Gifi (1990) and one brief introduction is in the Appendix. Based on the information provided by the Survey of Quality of Vida (ECV) realised year 2005 for the municipalities of Barbosa, Beautiful, Calda, Copacabana, Girardota, Itagüí, the Star, Sabaneta and Medellín, indicators were constructed to as much measure the quality of life of the homes in the urban area as rural. These indicators are a summary of different characteristics related to the house, demographic aspects of the people who compose the home, the access to the services public, and the human capital and the social security of the home. The indicator assigns to each home a puntaje varies between zero and one hundred: As the value of the index increases, the conditions of life of the home improve. The ECV has come applying every two years regularly. In 2009, the ECV for all the municipalities of Metropolitan Area with the aim of estimating the evolution of the indicator with respect to year 2007 was repeated. In order to realise this evaluation, the Indicator of Quality of Life was used obtained in the 2005 valued with the new information of the ECV of the 2009.